2021
DOI: 10.1029/2020jc016194
|View full text |Cite
|
Sign up to set email alerts
|

Surface Thermal Structure and Variability of Upwelling Shadows in the Gulf of Arauco, Chile

Abstract: Enhanced coastal upwelling usually occurs near capes (e.g., Castelao & Barth, 2007), due to vorticity effects along with the acceleration of winds and currents (Largier, 2020). Moreover, the wind shadows and upwelling circulation around capes can also generate upwelling shadows on the side protected from the upwelling jet and alongshore wind. An upwelling shadow has been defined as "a localized region of an active coastal upwelling system within which upwelling is reduced, and a coherent pattern of anomalously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…The SST pattern was also coherent with the one observed in a previous work (Wong et al, 2021), where the reported mean thermal difference between GA and PL was about 1 °C. The wind intensification in PL and the stronger SST gradient between PL and GA, observed for US days, also agree with the US conditions described by Wong et al (2021). The analysis of composites and the study of two cases allows us to connect well-studied synoptic-scale atmospheric phenomena with the occurrence of US events in the GA.…”
Section: A Mechanism For Us Eventssupporting
confidence: 89%
See 3 more Smart Citations
“…The SST pattern was also coherent with the one observed in a previous work (Wong et al, 2021), where the reported mean thermal difference between GA and PL was about 1 °C. The wind intensification in PL and the stronger SST gradient between PL and GA, observed for US days, also agree with the US conditions described by Wong et al (2021). The analysis of composites and the study of two cases allows us to connect well-studied synoptic-scale atmospheric phenomena with the occurrence of US events in the GA.…”
Section: A Mechanism For Us Eventssupporting
confidence: 89%
“…US days inside GA were defined using an index developed by Wong et al. (2021). An US event was set as three or more consecutive US days, finding 40 events during the austral summer from January 2011 to September 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During upwelling events, surface waters in upwelling centers are advected equatorward and alongshore until encountering topographic features that alter surface flow (Graham & Largier, 1996;Woodson et al, 2012;Mazzini and Barth, 2013;Wong et al, 2021). In the lee (equatorward) of topographic features, where wind-forcing is reduced, the upwelling plume may bifurcate, with a portion of the plume continuing equatorward along the coast, and the remaining recirculating poleward.…”
Section: Introductionmentioning
confidence: 99%